Progress in adolescent sexual and reproductive health and rights globally between 1990 and 2016: what progress has been made, what contributed to this, and what are the implications for the future?. Issue 1 (1st January 2020) - Chandra-Mouli, Venkatraman; Akwara, Elsie; Engel, Danielle; Plessons, Marina; Asnake, Mengistu; Mehra, Sunil; Dick, Bruce; Ferguson, Jane
Abstract: This commentary is in response to a paper published in the Lancet entitled: "Progress in adolescent health and well-being: tracking 12 headline indicators for 195 countries and territories, 1990-2016" (Peter Azzopardi et al, 2019). We agree with the authors' overall conclusions that although there has been progress in some health outcomes, health risks and social determinants, the situation has worsened in other areas. Other important messages emerge from studying the data with an adolescent sexual and reproductive health and rights (ASRHR) lens. First, notable – albeit uneven – progress in all the ASRHR indicators has occurred in multi-burden countries. Second, while we cannot assign a cause-effect relationship, it is reasonable to suggest that in addition to secular trends, deliberate global and national investment and action have contributed to and/or accelerated these changes. Third, progress in ASRHR in the multi-burden countries contrasts sharply with increases in rates of tobacco use, binge drinking and overweight and obesity, in all categories of countries. Based on these observations, we submit five implications for action: the adolescent health community must recognize the progress made in ASRHR; acknowledge that increasing investment and action in ASRHR has contributed to these tangible results, which has the potential to grow; build on the gains in ASRHR through concerted action and a focus on implementation science; expand the adolescent health agenda in a progressive and strategic manner; and contribute to wider efforts to respond to adolescents' health needs within the rapidly changing context of the worlds they live in.